Synthesizing historical plant collections to identify priorities for future collection efforts and research applications - Elizabeth M. Lombardi; Harpo Faust; Hannah E. Marx (Ecosphere)
Abstract To understand how and where biodiversity is threatened, it is imperative to build historical baselines that accurately characterize the present and past states of biodiversity across environments. Botanical collections provide important ecological, evolutionary, and biogeographic information on the diversity and distributions of plant taxa, yet biases in collection efforts across spatial, temporal, and taxonomic scales are well known. Here, we characterize and quantify trends in botanical collections made from across different abiotic, biotic, and sociopolitical boundaries within the present‐day state of New Mexico. Using a biodiversity informatics approach applied toward a regional case study, we identify opportunities for efficiently improving natural history collection coverage and analyses of botanical diversity. Accurate representation of botanical biodiversity, preserved for future generations through vouchered plant specimens deposited in herbaria, depends on collection decisions made now. This work aims to provide a useful workflow for synthesizing digitized regional botanical collections as researchers prioritize current and future resources in the face of global change.